FORMULATION AND ANTIOXIDANTS EVALUATION OF LIQUID SOAP OF SALACCA ZALACCA (GAERTN.) VOSS. PEELS ETHANOL EXTRACT 96% - Andi Nafisah Tendri Adjeng; Nur Illiyin Akib; Sania Hairah; Syahlan Herman (Bajang Institute, 2022)
Background: Free radicals are compounds that can adversely affect the skin, so antioxidants are needed to maintain healthy skin. Salacca zalacca (Gaert.) Voss. peels extract contains flavonoids which are potential as antioxidants. To maximize the role of topical antioxidants from extracts of Salacca zalacca (Gaert.) Voss. Peels against free radicals that expose the skin, therefore an acceptable preparation is needed, one of which is soap. Objective: this study aims to determine the antioxidant activity of the 96% ethanol peels extract of Salacca zalacca (Gaert.) Voss. and the formulated soap which containing the fruit peels extract. Method: Antioxidant activity was determined by DPPH test (1,1-diphenyl-2-picrylhydrazyl). Results: IC50 of Antioxidants values of the extract are 62.08 ppm. Antioxidants IC50 of the formulated soap are 139.65 ppm for Formula 1 (F1); 73.2 ppm for Formula 2 (F2); and 55 ppm for Formula 3 (F3). The results show that the 96% ethanol extract of Salacca zalacca (Gaert.) Voss has the potential as source of natural antioxidants that can be developed in liquid soap preparations. Conclusions: Peels and the soap formulated containing the extract of the fruit peels has antioxidant potency. The antioxidant activity of liquid soap preparations increases with the increase in ethanol extract 96% of Salacca zalacca (Gaert.) Voss in the liquid soap. Formula 3 (FIII) contained 3% of Salacca zalacca (Gaert.) Voss ethanol extract 96% is the best Formula against free radicals with 62.08 ppm of IC50 which is categorized as moderate anti-oxidant